Comparison Of Venture Capital And Business Incubation In Financing And Supporting Small And Medium Corporates With The Possibility Of The Development Of Integration Between Them - Mahmoud, Youssef; Shriqy, Torfah; Hammouda, Nawar (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This project is dealing with the comparison between the technics of venture capital and the business incubators in supporting the small and the medium enterprises, with the possibility of co-operating between each other, and evaluating their impact in financing these corporates. Venture capital is a special contributor in the financing corporates, this is due to its characteristic. We consider that the venture capitals basic roles are the finance and the direction, that means that its depending on financing rather than deputing. Venture capital is a new U.S.A financing technical In 1946 , then this last one stretched to the other developed and growing countries and it realized a big success because of the industrial revolution supports like: informatics, technology, T.I.C, bio-technology. Business incubators role is the same as venture capital, and it was a strategic importance in supporting these private corporates specially the best projects and how to reflect them into real ones on the ground, to be able to continue and to make effected competitions to realize economic goals. So, this projects concerning the close between the two factors. يتناول هذا البحث دراسة مقارنة بين تقنية رأس المال المخاطر وحاضنات الأعمال في دعم الشركات الصغيرة والمتوسطة، مع إمكانية التكامل بينهما وتقييم فعاليتهما في تمويل هذه الشركات، فرأس المال المخاطر يعتبر كمساهم خاص في الشركات الممولة وذلك للخصائص التي يتميز بها، ويتمثل دوره الأساسي في التمويل، المرافقة والتوجيه، إذ يقوم في الواقع على أسلوب المشاركة بدلاً من أسلوب المداينة، فهو عبارة عن تقنية تمويلية جديدة ظهرت بداية في الولايات المتحدة الأمريكية عام 1946 ، ثم انتشرت في مختلف دول العالم المتحضر منه والنامي، وحققت نجاحاً كبيراً نتيجة للدعم التي قدمته للثوا رت الصناعية التي شهدها العالم كالإعلام الآلي، التكنولوجيا الحيوية، تقنيات الإعلام والاتصال، المعالجات الدقيقة وغيرها أما حاضنات الأعمال فيتمثل دورها أيضاً في المرافقة والتوجيه، ولها أهمية استراتيجية في دعم وتشجيع هذه الشركات خاصة منها المشاريع الريادية وتحويلها على أرض الواقع لما تقدمه من تسهيلات ومساعدات لازمة حتى تصبح قادرة على الاستمرار والمنافسة وتحقيق غايات اقتصادية، ونتيجة للتقارب بين هاتين الآليتين تم التطرق لهذا البحث، والذي خلص إلى أن تجربة مؤسسات رأس المال المخاطر وحاضنات الأعمال قدمتا البديل الحقيقي والعملي لنظام التمويل التقليدي خاصة في الاستثمارات طويلة الأجل.